2010
DOI: 10.5114/aoms.2010.14464
|View full text |Cite
|
Sign up to set email alerts
|

Renal vascular response to angiotensin II inhibition in intensive antihypertensive treatment of essential hypertension

Abstract: IntroductionHigh blood pressure (BP) leads to target organ damage. It is suggested that regression of early organ lesions is possible on condition of BP normalization. The study objective was to assess whether permanent reduction of BP to the recommended values modifies renal vascular response to acute angiotensin II inhibition in the Doppler captopril test (DCT) in patients with essential hypertension (EH).Material and methodsTwenty-nine persons (58 kidneys) were found eligible for the study: 18 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…If the antihypertensive response to the initial drug is inadequate after reaching the full dose, a second drug from another class should be added, provided the initial drug is tolerated [84, 85]. ACCF/AHA guidelines confirm the current ESH [64] and current NICE recommendations [84] that all main antihypertensive drug classes – diuretics, angiotensin-converting enzyme inhibitors (ACEIs), angiotensin-receptor blockers (ARBs), calcium channel blockers (CCBs), and β-blockers – have shown significant benefits in reducing CV outcomes in randomized trials among elderly persons [86–91]. Where possible, a combination therapy should be the method of choice [84, 85].…”
Section: Hypertension Update 2011mentioning
confidence: 99%
“…If the antihypertensive response to the initial drug is inadequate after reaching the full dose, a second drug from another class should be added, provided the initial drug is tolerated [84, 85]. ACCF/AHA guidelines confirm the current ESH [64] and current NICE recommendations [84] that all main antihypertensive drug classes – diuretics, angiotensin-converting enzyme inhibitors (ACEIs), angiotensin-receptor blockers (ARBs), calcium channel blockers (CCBs), and β-blockers – have shown significant benefits in reducing CV outcomes in randomized trials among elderly persons [86–91]. Where possible, a combination therapy should be the method of choice [84, 85].…”
Section: Hypertension Update 2011mentioning
confidence: 99%
“…In effect it was already demonstrated that a significant blood pressure lowering to recommended values is associated with a significant improvement of intrarenal arterial functional properties and renal function (14). Similarly obesity is a major risk factor for essential hypertension, diabetes, and other comorbid conditions that contribute to the development of chronic kidney disease (37).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it is also known that RRI decreases with use of renin angiotensin system (RAS) inhibitors, due to the hemodynamic changes induced by these antihypertensive agents. (13) Anyway there are some points that still need to be clarified and among these it is not known whether and how much dietetic and therapeutic interventions may affect RRI (10) except for the fact that RRI, as already mentioned, is known to decrease with use of RAS inhibitors (13) and that it is also known that intensive blood pressure lowering to the recommended values is associated with a significant improvement of intrarenal arterial functional properties and renal function (14). Moreover longitudinal population studies are still needed to clarify whether Doppler changes in intrarenal arteries may be associated to an improvement in the cardiovascular and renal outcome in the hypertensive patients (15).…”
Section: Introductionmentioning
confidence: 99%
“…If the antihypertensive response to the initial drug is inadequate after reaching the full dose, a second drug from another class should be added, provided the initial drug is tolerated [84,85]. ACCF/AHA guidelines confirm the current ESH [64] and current NICE recommendations [84] that all main antihypertensive drug classes -diuretics, angiotensin-converting enzyme inhibitors (ACEIs), angiotensin-receptor blockers (ARBs), calcium channel blockers (CCBs), and β-blockers -have shown significant benefits in reducing CV outcomes in randomized trials among elderly persons [86][87][88][89][90][91]. Where possible, a combination therapy should be the method of choice [84,85].…”
Section: Hypertension Update 2011mentioning
confidence: 99%